Peningkatan Mutu Pendidikan Tinggi Hukum Berbasis Pancasila - I Putu Sastra Wibawa (Jurnal Penjaminan Mutu, 2019)
Human development with cross-cultural characteristics is one of them can be done by optimizing the higher education law that has the character of Pancasila. Pancasila has values that must be internalized into legal higher education that are spread throughout the existing courses. Pancasila values are systems that cannot be separated from one another. One form of effort to build a higher education law with Pancasila character by incorporating the principles of legal pluralism in the legal studies conducted.